تصوف کی روشنی میں اصلاح نفس: عوارف المعارف اور فتوح الغیب کا اختصاصی مطالعہ: Self-Reformation in the Light of Sufism A Specialized Study of 'Awarif al-Ma'arif' and 'Futuh al-Ghaib' - Dr. Zia U Din,; Dr.Shakeel Ur Rahman, (MEI, 2025)
This article delves into the principles of self-purification (Tazkiyah al-Nafs) in light of Islamic mysticism (Tasawwuf), with a specialized study of two seminal works: Awarif al-Ma'arif by Shaykh Shihab al-Din Suhrawardi and Futuh al-Ghayb by Shaykh Abd al-Qadir al-Jilani. It explores the spiritual teachings of these texts, focusing on their guidance for inner reform, the purification of the soul, and practical approaches to achieving closeness to Allah. The study offers a comparative analysis of the methodologies and principles outlined in these works, highlighting their similarities, differences, and unique contributions to the field of Islamic spirituality. Furthermore, the article emphasizes the contemporary relevance of these teachings, presenting practical ways to apply them to modern societal, psychological, and moral challenges. By bridging the classical principles of self-purification with current needs, this study underscores the enduring significance of Tasawwuf as a guide for personal and communal reform in today's world. Keywords: Tazkiyah al-Nafs, Tasawwuf, Awarif al-Ma'arif, Futuh al-Ghayb, Self-Purification, Spiritual Reform, Islamic Mysticism, Contemporary Relevance.